2014
DOI: 10.1002/abc.21163
|View full text |Cite
|
Sign up to set email alerts
|

Visual Thinking, Art, and University Teaching across Disciplines

Abstract: Visual Thinking, Art, and University Teaching Across DisciplinesH OW MIGHT VIEWING and discussing art be relevant to university curricula across disciplines? This was one of my fundamental questions when I became the fi rst director of academic programs at the Rose Art Museum, Brandeis University, in August 2010. My overarching inquiry was how could my work demonstrate that university art museums truly matter to their parent institutions, particularly in terms of teaching and learning?These were urgent matters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Studies have revealed that VTS was effective for improving writing (Franco & Unrath, ; Moeller, Cutler, Fiedler, & Weier, ), critical thinking (Landorf, ; Moeller et al., , Yenawine & Miller, ), and encouraging risk taking (Franco & Unrath, ; Landorf, ). In companion articles, Hailey () and Yenawine and Miller supported the use of VTS across disciplines. The strategies are useful across disciplines because “VTS does not teach what to think, but rather supports the discoveries students make when they are given opportunities to think in various ways” (Yenawine & Miller, , p. 3).…”
Section: About Vtsmentioning
confidence: 99%
“…Studies have revealed that VTS was effective for improving writing (Franco & Unrath, ; Moeller, Cutler, Fiedler, & Weier, ), critical thinking (Landorf, ; Moeller et al., , Yenawine & Miller, ), and encouraging risk taking (Franco & Unrath, ; Landorf, ). In companion articles, Hailey () and Yenawine and Miller supported the use of VTS across disciplines. The strategies are useful across disciplines because “VTS does not teach what to think, but rather supports the discoveries students make when they are given opportunities to think in various ways” (Yenawine & Miller, , p. 3).…”
Section: About Vtsmentioning
confidence: 99%
“…Versions for middle school and high school are being tested. Variations have been devised for use in museum teaching, university classes (Miller and Yenawine 2014;Hailey 2014), medical education (see next page), and the professional world.…”
Section: The Vts Protocolmentioning
confidence: 99%
“…The facilitator thanks the group for their participation (Hailey et al, 2015) This set of discursive practices of VTS is closely related to leadership practices. VTS can result in empowering participants to communicate and recognize multiple perspectives (Hailey, 2014). Asking an open-ended question such as "What is going on in this picture?…”
Section: Introductionmentioning
confidence: 99%
“…for intentionally selected images with elements that could be interpreted variously offers an opportunity to develop an ability to tolerate ambiguity and uncertainty (Hailey, 2014;Yenawine & Miller, 2014). In this regard, by engaging in VTS sessions, students can develop skills for dealing with complex information, navigating adaptive challenges (Heifetz, 1994), and divergent set of meanings and interpretations (Barge & Fairhurst, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation